Agroactive volatile organic compounds from microbes: Chemical diversities and potentials of application in crop protection - Kaimei Wang; Shaoyong Ke; Wei Fang; Fang Liu; Zhigang Zhang (Advanced Agrochem, 2023)
Synthetic chemicals have been widely used in modern agriculture as fertilizer, plant growth regulators and pesticides. Although the chemical inputs improved the crop production, it is well known about their negative effects, such as environmental residues in water, soil and animals, pest resistance and resurgence and the residues in agricultural produces. The demands for safer food and more friendly environment are now more preferred by humankind in the world. Microbes have already become an alternate for chemical inputs in some aspects in agriculture. The microbes can produce very diverse volatile organic compounds (mVOCs) which play important roles in the interactions between plant and microbes, or among intraspecies or interspecies of microbes. Many mVOCs showed diverse agroactivities, such as insecticidal, bactericidal, fungicidal, herbicidal, plant growth promotion and abiotic stress-tolerance inducing activities. The agroactive mVOCs have diverse structure-types, such as alkane, alkenes, alcohols, aldehydes, ketones, carboxylic acid, esters and lactones, ethers, aromatic ring, terpenes, heterocycles, sulphur-containing VOCs. The promising agroactive properties make it possible to apply mVOCs and their producing microorganisms or synthetic mimics or agroactive mVOCs in crop protection, and so this review focuses on the chemical diversity, agroactivities, and potential application of mVOCs.